The scientific basis of practical strategies to maintain immunocompetence in elite athletes - Gleeson, M. (Exercise Immunology Review, 2000)
The functioning of the immune system is affected by stress. An accumulation of stress in elite athletes may lead to chronic immunosuppression and hence increased susceptibility to opportunistic infections. Therefore, athletes, coaches, and their medical support personnel are seeking guidelines to reduce the risk of illness, which, when it occurs, is likely to compromise training and competition performance. Training strategies to minimize the risk of immunosuppression need to consider the management of training volume and intensity, training variety to overcome monotony and strain, a periodised and graded approach to increasing training loads, and provision of adequate rest and recovery periods. In order to limit the effects of psychological stress, athletes should be taught self-management and coping skills. Benefit may be gained from monitoring athletesÕ responses to the psychological and psychosocial stresses of high-level training and competition. Nutritional considerations should emphasize the need for adequate intakes of fluid, carbohydrate, protein, and micronutrients. Limiting initial exposure when training or competing in adverse environmental conditions (heat, humidity, cold, altitude or polluted air) and acclimatizing where appropriate will reduce the effects of environmental stress. Other behavioral, lifestyle changes such as good hygiene practice, may limit transmission of contagious illnesses by reducing exposure to common sources of infection. Medical support including regular check ups, appropriate immunization, and prophylaxis may be particularly important for athletes who are at high risk of succumbing to recurrent infection. Exercise Immunology Review, 2000, 6 (1).